TREND OF SELECTION FOR STUDY PLANNING USING MACHINE LEARNING BY COMPARING THE RESULTS BETWEEN ARTIFICIAL NEURAL NETWORK AND SUPPORT VECTOR MACHINE - Ruckbumrung, Thitichai; Naewpraneet, Patsagon; Puripanik, Chonticha; Choopun, Pronsuda (HRD Journal, 2023)
This research is to finding trends for decision in the selection of high school study plans between sciences and mathematics plan and arts plan by using machine learning to help analyze data using Supervised Learning by comparing 2 techniques; Artificial Neural Network and Support Vector Machine with a total of 908 sample data sets. The objectives of research were 1) to create a model of trends analyze for decision to select high school study plans between sciences and mathematics plan and arts plan 2) to compare the performance of the selection of high school study plans model by Artificial Neural Network and Support Vector Machine techniques. It was found that when the data were used to find the percentage of accuracy by dividing of the training set; the training set was 80 percent and the testing set was 20 percent. The accuracy analyzing was as follows: 1)Artificial Neural Network 80 percent 2)Support Vector Machine 85 percent.